MUHAMMADIYAH TV SUSTAINABILITY VISION DESIGN PERSPECTIVE OF AL MAUN THEOLOGY - Eksanti; Luqman Hakim; M Irfan Tarmizi (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2023)
Vision becomes a form or picture of what the company will be like. Vision can also be said to be the purpose of a company, so that the selection of vision can affect the form of business and the results that will be obtained from the business. "Vision" is likened to the image of a company to convey enduring values and enduring goals and in an effective manner. Vision is also a picture for a company to survive in its business competition. The purpose of this study is to critically analyze the vision and mission used by TVMu in surviving and carrying out its business activities using the perspective of Al-Maun theology. This research uses a qualitative approach. Data collection was conducted using documentation studies and in-depth interviews. Interviews were conducted with 4 informants on TVMu. Data analysis using the perspective of Miles and Huberman using the perspective of Al-Maun theology. The results showed that in maintaining the vision as a da'wah TV based on amar maruf nahi munkar, the foremost, intelligent, enlightening and part of AUM does not mean that it never makes mistakes as a result of pragmatic orientation towards sponsors. The pressure of operating costs and profits is one of the reasons TVMu receives advertisements and programs that override the vision and mission of TVMu's initial establishment.